Prefetching for mobile web album - Lin, Yi-Bing; Huang, Po-Kao (My University, 2016)
A web album service allows a user to publish photo albums on the web and view albums of other users. Through broadband mobile telecom, users can enjoy watching contents of web albums at any place in real time. User experience on mobile web album is affected by the transmission delay of mobile network, which determines whether the user needs to wait to view the images. We propose a prefetching mechanism that enhances user experience on accessing mobile web albums. A transmission control protocol-like sliding window protocol (of size N) is exercised, and when the buffer for the sliding window at the user equipment is full, prefetching is suspended. The buffer size N affects the prefetching performance. The larger the N value, the better the user experience. However, a large N value means that many images will be prefetched. If they are not actually viewed by the user, the network resources for transmitting these images are wasted. This paper proposes both analytic and simulation models to select the smallest N (the optimal N value) so that the expected user experience can be achieved. Copyright (C) 2014 John Wiley & Sons, Ltd.
Keywords: mobile application; web album; prefetching; performance